2016
DOI: 10.1165/rcmb.2016-0077oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Restricted Antibodies Mediate Primary Graft Dysfunction and Prevent Allotolerance after Murine Lung Transplantation

Abstract: Over one-third of lung recipients have preexisting antibodies against lung-restricted antigens: collagen (Col) type V and K-a1 tubulin (KAT). Although clinical studies have shown association of these antibodies with primary graft dysfunction (PGD), their biological significance remains unclear. We tested whether preexisting lungrestricted antibodies can mediate PGD and prevent allotolerance. A murine syngeneic (C57BL/6) or allogeneic (C57BL/6 to BALB/c) left lung transplantation model was used. Rabbit polyclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Pre‐existing Abs to lung SAgs can increase the risk for primary graft dysfunction (PGD), as they increase the development of pro‐inflammatory cytokines and increase the risk of development of Abs to HLA and non‐HLA antigens, which are known risk factors for CLAD . Recently, pre‐existing Abs to lung‐associated SAgs (in the absence of Abs to donor HLA) were shown to result in antibody‐mediated acute rejection . Since patients with primary lung disease are known to be susceptible for comorbid conditions, our studies might explain why some patients waiting for LTx have pre‐existing autoantibodies.…”
Section: Pre‐existing Autoimmunity Induces Primary Graft Dysfunction mentioning
confidence: 92%
See 1 more Smart Citation
“…Pre‐existing Abs to lung SAgs can increase the risk for primary graft dysfunction (PGD), as they increase the development of pro‐inflammatory cytokines and increase the risk of development of Abs to HLA and non‐HLA antigens, which are known risk factors for CLAD . Recently, pre‐existing Abs to lung‐associated SAgs (in the absence of Abs to donor HLA) were shown to result in antibody‐mediated acute rejection . Since patients with primary lung disease are known to be susceptible for comorbid conditions, our studies might explain why some patients waiting for LTx have pre‐existing autoantibodies.…”
Section: Pre‐existing Autoimmunity Induces Primary Graft Dysfunction mentioning
confidence: 92%
“…Our group has shown that pre‐existing autoimmunity is one of the most predominant risk factors for the development of CLAD . Pre‐existing Abs to lung SAgs can increase the risk for primary graft dysfunction (PGD), as they increase the development of pro‐inflammatory cytokines and increase the risk of development of Abs to HLA and non‐HLA antigens, which are known risk factors for CLAD .…”
Section: Pre‐existing Autoimmunity Induces Primary Graft Dysfunction mentioning
confidence: 99%
“…Antibodies to collagen V have been found deposited in lung allograft in human as well as in a mouse model (Sumpter & Wilkes, 2004). Preexisting of K‐α1‐tubulin antibodies can cause development of primary graft dysfunction in a dose dependent manner in a mouse model (Bharat et al., 2016). Patients who clear antibodies against K‐α1‐tubulin and collagen V after the rituximab and/or IVIG therapy are significantly less likely to develop bronchiolitis obliterans syndrome than those who have persistent K‐α1‐tubulin and collagen V antibodies, which further confirms the pathological effect of antibodies against K‐α1‐tubulin and collagen V (Hachem et al., 2012).…”
Section: Antibodies To Vimentinmentioning
confidence: 99%
“…Because a number of clinical factors can confound the association between preexisting Abs to lung SAgs and PGD, we tested whether these two variables are mechanistically linked using the murine model of unilateral LTx [71]. In this recent study, recipients were passively given one or more Abs to lung-restricted antigens before transplantation of syngeneic lung grafts.…”
Section: Role Of Tissue-restricted Abs In Organ Transplantationmentioning
confidence: 99%